Biodegradation of buried crude oil in soil microcosm by fungal co-culture. Issue 1 (December 2020) - Yanto, D H Y; Hidayat, A
Abstract: Crude oil pollution in soil is a major environmental problem over the world. After long-term contamination, crude oil can be buried in the soil and leaving the toxic and persistence compounds. Treatment of buried crude oil in soil is a major challenge. In this study, buried crude oil in soil (20 cm-depth) was treated by the co-culture of three fungal strains ( Pestalotiopsis sp. NG007/ Polyporus sp. S133/ Trametes hirsuta D7 with composition 1/1/1 and pre-grown in wood meal) placed on the top or bottom layer of the soil. Biodegradation behavior of crude oils were analyzed at different depth interval (0–5 cm, 5–15 cm, and 15–20 cm) with constant oxygen diffusion. The results showed that both position of fungal co-culture could degrade crude oil 63 – 92% after 30 days. Placing the co-culture in the bottom layer position of the soil demonstrated more effective degradation for all the depth interval than that of the top layer position. During the biodegradation, the co-culture produced oxidative enzymes such as catechol 1, 2-dioxygenase, catechol 2, 3-dioxygenase, laccase, manganese peroxidase, and lignin peroxidase with significant activities. This study offers an important strategy to remediate crude oil contaminated soil, specifically buried crude oil.